Genotoxic and chemopreventive potentials of ethanol leaves extract of Annona muricata on N-Ethyl-N-Nitrosourea-induced pro-leukaemia carcinogen in mice model by bone marrow micronucleus assay - Bamisaye, Oluwaseyi; Fashina, Anthony; Abdulraheem, Fatai; Akanni , Olufemi Emmanuel; Olufemi, Fadiora S. (Journal of Medical Science, 2022)
Background. Studies have proven the effect of several agents, including natural products, to induce, prevent and treat genotoxicity through experimental models and clinical trials. In this study, the genotoxic preventive potential of Annona muricata ethanol extract on N-Ethyl-N-Nitrosourea (ENU)-induced pro-leukaemia in mice models using micronuclei formation in bone marrow was assessed.Materials and methods. Forty-eight mice weighing 18-24g were randomly divided into six groups of eight mice. The mice were intravenously administered 20mg/kg of NEU 48 hourly 3 times, 80mg/kg of NEU 48 hourly 3 times. The negative control was fed with feed and water only. We introduced 0.2ml (0.1g/ml) ethanolic extract of Annona muricata for 3 weeks prior to NEU low dosage administration, 0.2ml (0.1g/ml) ethanolic extract of Annona muricata for 3 weeks prior to ENU high dosage and Annona muricata (ethanolic extract) administration, and gave commercial diet to the adverse/ toxicity group.  The bone marrow was harvested, smeared and stained using MayGrumwald. The procedure enabled the determination of micronucleus polychromatic erythrocytes (MNPCEs) microscopically.Results. Groups exposed to various dosages of the ENU yielded significantly increased MNPCEs, with group B producing higher MNPCEs. The groups treated with the extract displayed a significant reduction in the MNPCEs despite prior exposure to concentrations of NEU. The adverse group displayed no difference in MNPCEs compared with the negative control.Conclusion. The ENU induced genotoxicity depending on its concentration. The extract displayed a profound capacity to prevent genotoxicity and alleviate leukaemia with good tolerance.